High Efficiency Top-Emission Organic Light Emitting Diodes with Second and Third-Order Microcavity Structure. (13th October 2015) - Son, Young Hoon; Park, Mi Jin; Pode, Ramchandra; Kwon, Jang Hyuk
Abstract : Top-emitting micro-cavity organic light emitting diodes (TEOLEDs) are now acquiring the center stage as an important candidate for the active matrix display applications. OLEDs with top-emission structure, thicknesses of organic layers over 2000 Å are crucial for the real mass production of OLED. In this paper, we report top-emitting organic light emitting diodes with various strong microcavity structures such as second order, third order microcavity mode, and tandem architecture. We design the device layer structure, especially the location of emissive layer, by simulating the radiance distribution of red, green, and blue emitter as a function of thickness of transporting layers. Furthermore, the quantum efficiency of designed device is estimated. In summary, both optically and electrically simulated results of TEOLEDs are quite well matched with those of actually fabricated devices.